Near constancy of the Pacific Ocean surface to mid-depth radiocarbon-age difference over the last 20 kyr - Broecker, W.; Clark, E.; Barker, S. (Earth and Planetary Science Letters, 2008)
Although C-13 to C-12 and cadmium to calcium ratios provide information regarding the distribution of deep water masses during late glacial time and during the period of deglaciation, our knowledge of the rate at which these water masses were ventilated comes mainly from the difference in radiocarbon-age between coexisting bottom- and surface-dwelling foraminifera. Paired benthic/planktonic foraminiferal radiocarbonage differences covering last 20 kyr in a high-deposition-rate western equatorial Pacific core, MD01-2386, from a water depth of 2.8 km show no significant climate-related variations over this period. This result is surprising for we would have expected a change in this age difference between the last glacial maximum (LGM) and the Holocene and also during the Mystery Interval (17.5-14.5 kyr ago) when the waters in a radiocarbon-depleted abyssal reservoir were presumably being mixed back into the remainder of the ocean. (C) 2008 Elsevier B.V. All rights reserved.
id: 770; 390GV Times Cited:2 Cited References Count:27Y